2018
DOI: 10.3357/amhp.4955.2018
|View full text |Cite
|
Sign up to set email alerts
|

Neck Kinematics and Electromyography While Wearing Head Supported Mass During Running

Abstract: This study suggests that HSM can fatigue bilateral neck flexors and rotators, as well as fatigue the neck extensors and rotators on the contralateral side of the mounted NVG.Hanks MM, Sefton JM, Oliver GD. Neck kinematics and electromyography while wearing head supported mass during running. Aerosp Med Hum Perform. 2018; 89(1):9-13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is well established that the main negative effect on the mobility of firefighters is due to PPEs that lead to a decrease in physical performance [ 29 ]. Many different approaches have been proposed to quantitatively measure the mobility of firefighters during typical activities and the majority focused the analysis on the evaluation of the range of motion (ROM) [ 88 , 93 , 95 , 96 , 98 , 101 , 102 , 103 , 105 ].…”
Section: Sensor-based Systems For Physical Parameter Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the main negative effect on the mobility of firefighters is due to PPEs that lead to a decrease in physical performance [ 29 ]. Many different approaches have been proposed to quantitatively measure the mobility of firefighters during typical activities and the majority focused the analysis on the evaluation of the range of motion (ROM) [ 88 , 93 , 95 , 96 , 98 , 101 , 102 , 103 , 105 ].…”
Section: Sensor-based Systems For Physical Parameter Monitoringmentioning
confidence: 99%
“…For all the above-mentioned reasons, several studies deal with the analysis of physiological variables [6, and physical parameters [88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107]. Sensor-based systems, such as portable metabolic systems, heart rate monitors, ingestible temperature pills and skin temperature patches for the physiological aspects [6,25,46,48,53,[55][56][57]71,74,78,81,84], as well optoelectronic systems, inertial sensors and pressure insoles for the physical ones [94][95][96][97][98]101,102,108,109] have shown their potential mainly due to the possibility to measure several variables without influencing the FF working procedures. Moreover, the latest progress in the robotic field has opened the possibility to use robotic devices to help prevent worker fatigue and work-related musculo-skeletal disorders in manufacturing settings.…”
Section: Introductionmentioning
confidence: 99%
“…For instances, prolonged static postures (Christensen et al, 2023), repetitive neck motions (Guidotti, 1992), heavy lifting or working in awkward neck postures (Ariens et al, 2000), sedentary lifestyle and poor sleep quality (Peterson and Pihlström, 2021), and chronic stress and certain mental health conditions (Kim et al, 2013) have been associated with work-related neck MSD. In addition to these causes, the usage of helmets and other head mounted devices in medical surgery (Nimbarte et al, 2013), military (Hanks et al, 2018), firefighter (Park et al, 2014; Wang et al, 2021), sports (Kent et al, 2020; Mortensen et al, 2020), and vehicle safety applications (Diyana et al, 2019) were found to increase the chances of neck MSD.…”
Section: Introductionmentioning
confidence: 99%